Samsung Galaxy Tab 10.1 for dummies - Gookin, Dan (Wiley, 2012)
A vast improvement over the original Galaxy Tab, the 10.1 uses the latest version of the Android operating system and is a 4G LTE mobile device. These upgrades—along with many others, including the better screen quality, better web browsing with Flash, and better multitasking capabilities—are all covered in this fun and friendly guide to the Samsung Galaxy Tab 10.1. Everything from how-to topics to the most useful features to helpful tricks and techniques, this practical guide shows you how to get the most out of this cutting-edge device